Collisions of Small Kuiper Belt Objects With (486958) Arrokoth: Implications for Its Spin Evolution and Bulk Density. Issue 12 (10th December 2021) - Mao, Xiaochen; McKinnon, William B.; Singer, Kelsi N.; Keane, James T.; Beyer, Ross A.; Greenstreet, Sarah; Robbins, Stuart J.; Schenk, Paul M.; Moore, Jeffrey M.; Stern, S. Alan; Weaver, Harold A.; Spencer, John R.; et al.
Abstract: The orientation and morphology of the bilobate, cold classical Kuiper belt object (486958) Arrokoth (formerly 2014 MU69 ) is consistent with a slow, tidal merger of a close binary. However, the discrepancy between Arrokoth's present‐day rotation (15.9 hr) and synchronous rotation for nominal cometary densities near ∼500 kg/m 3 implies reduction (up to 30%) in post‐merger spin angular momentum. We investigate how collisions with dynamically cold and hot classical Kuiper belt objects might have affected Arrokoth's post‐merger spin. Using a dynamically equivalent triaxial ellipsoid, 5000 Monte Carlo simulations of 100 impacts each, consistent with Arrokoth's cratering record, were carried out. Starting from the assumption of critical, synchronous rotation for a given density, these simulations rarely reproduce Arrokoth's present spin period, unless its true density is near 250 kg/m 3 . We explore in greater depth the effects of formation of Arrokoth's largest crater (now officially named Sky, previously informally named Maryland). We adopt point‐source scaling and randomly select impact parameters that lead to the crater, using Arrokoth's full bilobate shape. Results from Sky's formation alone are similar to those considering a full range of impactor sizes, unless we adopt low cratering efficiency due to high porosity, which implies substantially larger Sky‐forming impactors. Overall, results imply that the probability of substantial angular momentum change due to impacts alone over Solar System history is unlikely, and spindown from a synchronous, tidal rotation rate to a 15.9‐hr period unlikely unless Arrokoth itself was and is a very low density object (∼250 kg/m 3 ), though we cannot statistically rule out densities up to 400 kg/m 3 . Plain Language Summary: Both lobes of the cold classical Kuiper belt object Arrokoth were likely in a close spin‐synchronous orbit before they gently merged to form the bilobate body we see today. This spin‐synchronous orbital period depends on density, however, and Arrokoth's observed spin period implies that it either has an extremely low density (much lower than typical cometary values) or underwent significant despinning after the merger. Here we study the spin‐altering effects of impacts by other, small Kuiper belt objects over time and address the likelihood of the required despinning by impacts, with implications for Arrokoth's bulk density. We use a Monte Carlo impact simulation to investigate Arrokoth's rotational response over its impact history, with special attention to the largest recognized crater (Sky). Our results indicate that: (a) Small impacts alone are not capable of altering Arrokoth's spin by much; (b) The likelihood of geophysically significant impact despinning on Arrokoth is low, if it has a typical cometary density of ∼500 kg m −3 ; (c) Arrokoth's bulk density may actually be quite low, ∼250 kg m −3, implying substantial porosity. Key Points: Impacts of classical Kuiper belt objects consistent with Arrokoth's observed craters caused at best modest spin changes The formation of the largest craters would have had a larger effect, especially if cratering efficiency is reduced by substantial porosity The most consistent interpretation of Arrokoth' shape and slow spin is that its bulk density is low, between 250 and 400 kg m −3